The Framework of Building Information Modeling (BIM) Implementation Stages for Malaysian Construction Industry - Nur Soleha Abdul Rahim; ShSarifah Akmam Syed Zakaria (Institut Teknologi Sepuluh Nopember, 2017)
Building Information Modeling (BIM) has attracted ever increasing attentions from construction industry stakeholders around the world including Malaysia. Numerous studies have been conducted in exploring the benefits of BIM and proposing strategies for BIM implementation. However, to convince the industry stakeholders to implement BIM technology is relatively challenging. Tangible evidences are needed to bring up the industry’s acceptability towards the technology. In Malaysia, the Construction Industry Transformation Programme (CITP) has been developed to drive the transformation and development of the construction industry. One of the cases highlighted in the CITP is on the limited adoption of information technology such as BIM. Therefore, currently the Malaysian government is actively engaging with construction industry stakeholders to encourage the BIM implementation. This paper aims to propose a framework of BIM implementation stages in the construction industry of Malaysia. Three case studies have been analysed as a fundamental study to develop the framework. The results show that two of the companies are at the adaptation stage and one of the companies is at the application stage. At this point of time, the results indicate that the companies are more comfortable to experience only some part of the BIM benefits compared to fully utilise the technology. Fundamentally, the companies will only be at the adoption stage once the confidence level towards the technology is increasing and the companies will be categorised in the application stage when the companies are able to perform knowledge transfer related to BIM technology. This implementation stages can be used as an indicator to predict the direction of BIM in Malaysia. Thus, to ensure the successfulness of BIM implementation, there is a need to understand the current stages of company’s BIM implementation and propose the criteria needed for a company to move from one BIM stage to another.